Building Tier 3 Intervention for Long‐Term Slow Growers in Grades 3–4: A Pilot Study. Issue 4 (28th October 2015) - Sanchez, Victoria M.; O'Connor, Rollanda E.
Abstract : Tier 3 interventions are necessary for improving the reading performance of students who fail to respond adequately to Tier 1 general education instruction and Tier 2 supplemental reading intervention. In this pilot study, we identified 8 students in 3rd and 4th grade who had demonstrated slow response to Tier 2 reading interventions for three years. Students participated in a researcher‐developed Tier 3 intervention for 8 weeks that focused on skill development in word analysis, word identification, and reading rate. In the 6 months prior to Tier 3, students were making minimal growth in reading; however, during Tier 3, the 8 students demonstrated strong growth on measures of word identification and reading rate. Although results are promising for poor readers who are difficult to remediate, several aspects of the Tier 3 intervention need further testing.